2019
DOI: 10.1177/2309499019888811
|View full text |Cite
|
Sign up to set email alerts
|

A steep coronal graft bending angle is associated with bone tunnel enlargement of the posterolateral bundle after anterior cruciate ligament reconstruction

Abstract: Purpose: The correlation between the graft bending angle (GBA) of the anteromedial bundle and posterolateral bundle after anterior cruciate ligament reconstruction (ACLR) and postoperative tunnel enlargement was evaluated. Methods: Two hundred fifty-eight patients (137 males, 121 females; mean age 27.3 years) who had undergone doublebundle ACLR were included. Computed tomographic scans of the operated knee were obtained at 2 weeks and 6 months postoperatively. The area of the tunnel aperture for femoral antero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…However, GBA was not statistically correlated with tunnel widening in the correlation analysis, which was contrary to what was expected. Yanagisawa et al 56 reported similar results to ours in their study on double-bundle ACL reconstruction. They noted that the change in tunnel widening was larger in the group with a higher GBA, but there was no significant correlation between AM tunnel widening and GBA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, GBA was not statistically correlated with tunnel widening in the correlation analysis, which was contrary to what was expected. Yanagisawa et al 56 reported similar results to ours in their study on double-bundle ACL reconstruction. They noted that the change in tunnel widening was larger in the group with a higher GBA, but there was no significant correlation between AM tunnel widening and GBA.…”
Section: Discussionsupporting
confidence: 85%
“…However, no significant difference was observed in other sections. Previous studies 27 , 48 , 56 reported that acute GBA was associated with tunnel aperture widening, which may be attributed to the increased contact pressure and excessive mechanical stress on the sharp edge of the bone tunnel aperture. 38 Considering an acute GBA in the OI technique that increases mechanical stress at the tunnel aperture, a larger tunnel widening at the tunnel aperture in the OI technique is understandable.…”
Section: Discussionmentioning
confidence: 93%
“…The optimal condition for femoral tunnel creation includes a sufficient length for proper graft healing and incorporation, and a stable tunnel wall without posterior wall blow-out for rigid fixation. In addition to these factors, more obtuse GBA is necessary to achieve better graft healing and graft maturation without tunnel widening 7 10 , 36 . According to the results of the study, although it is difficult to specify the lower limit of the flexion angle to create a stable tunnel, a knee flexion angle of > 120° might be appropriate to obtain a sufficient tunnel length and minimize the risk of posterior wall blow-out.…”
Section: Discussionmentioning
confidence: 99%
“…The abrasive forces could be created at the edge of the tunnel aperture because the direction of the ACL graft changes as it leads to the tunnel inside the bone from within the joint. Accordingly, the acute GBA causing a sharp change in graft path may influence graft healing, graft maturation, and tunnel widening resulting in unsatisfactory results 7 10 . The GBA is significant particularly at the femoral tunnel having a more sharp change of graft path at the tunnel aperture compared to that at the tibial tunnel 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the most proximal posterior FTE vs. most distal anterior demonstrates a halving of GBA and a five‐fold decrease of GBA‐excursion but the clinical relevance of this finding remains debatable. The role of GBA has been studied previously in regard to tunnel widening [33] and graft maturation [7, 17, 27]. Moreover, in posterior cruciate ligament (PCL) reconstruction a sharp GBA has been shown to not only attenuate the graft due to repetitive friction between the graft and tunnel inlet but even leading to graft displacement and residual laxity [18].…”
Section: Discussionmentioning
confidence: 99%